Bacillus polymyxa (Prazmowski) Mace 1889 Deoxyribonucleic Acid Relatedness and Base Composition - Nakamura, L. K. (International Journal of Systematic and Evolutionary Microbiology, 1987)
Estimates of deoxyribonucleic acid (DNA) relatedness and phenotypic characterization of 98 Bacillus polymyxa strains revealed that 70 (groups 1A and 1B) were closely related to the B. polymyxa type strain and 28 (group 2) were not. Group 1A strains (29) showed 80 to 100% DNA relatedness to the type strain, while the remaining 41 strains (group 1B) gave reduced relatedness values of 57 to 68%. Groups 1A and 1B were phenotypically identical. Low DNA homology values indicated that group 2 strains were not closely related to group 1A or 1B strains or to the type strains of Bacillus species that have guanine-plus-cytosine contents of 44 to 53 mol% or form gas from carbohydrates or both, namely, B. alvei, B. badius, B. brevis, B. coagulans, B. licheniformis, and B. macerans. Group 2 strains were phenotypically distinct from B. polymyxa and the seven recognized species.